Speech Rhythm in Kannada Speaking Children - Savithri SR; Sreedevi N; Aparna VS; Deepa Anand (Journal of All India Institute of Speech and Hearing, 1970)
Rhythm is a systematic temporal and accentual patterning of sound. Speech rhythm refers to the way languages are organized in time. The present study investigated the differences in the type of speech rhythm, in typically developing, Kannada speaking children in the age groups of 3-4 years, 8-9 years, and 11-12 years. Sixty children (10 girls and 10 boys in each of the three age groups) participated in the study. A five-minute speech sample was elicited using simple pictures/cartoons developed by Nagapoornima (1990) in 3-4 year old children; for children in the older age groups, pictures depicting simple stories developed by Rajendra Swamy (1991) adapted from Panchatantra were used. These speech samples were analyzed using PRAAT 5.1.14 software. Vocalic (V) and Intervocalic (IV) durations were measured. The durational difference between successive vocalic and intervocalic segments were calculated and averaged to get Pair wise Variability Index. Comparison of PVIs of the above age groups with Kannada speaking adults indicated that 3-4 year old children had syllabletimed rhythm pattern; 8-9 year and 11-12 year old children was mora-timed rhythm. Intervocalic PVI reduced from younger to older age group whereas vocalic PVI showed no such trend. Results obtained are discussed with reference to the rhythm types in each age group and establishing a continuum in development of speech rhythm.